PENGARUH PEMANFAATAN MEDIA SOSIAL (FACEBOOK) SEBAGAI MEDIA PROMOSI TERHADAP PENINGKATAN VOLUME PENJUALAN PADA SURYA FOTO STUDIO DI KOTA GUNUNGSITOLI - Bu'ulolo, Yufisman; Zalukhu, Yuterlin; Gea, Nov Elhan; Zebua, Serniati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
The development of the photographer business is currently increasing from year to year inIndonesia. The competition in this business is getting tighter, as seen from the increasingnumber of photographer businesses that are already growing in each region. Each studiobusiness tries to improve the quality and strategy in promoting their products and services.Like Surya Foto Studio which is one of the businesses that has many products and also photoservices in Gunungsitoli City. This study aims to determine how much the Influence of theEffectiveness of Utilizing Social Media (Facebook), as a Promotional Media on IncreasingSales Volume at Surya Foto Studio in Gunungsitoli City. This study uses a quantitativemethod. Respondents are people who have visited/experienced products and services fromSurya Foto Studio as many as 38 people. Where researchers use questionnaires, then conductdata validity tests, data reliability tests, classical assumption tests (normality tests), multiplelinear regression tests, hypothesis tests (t-tests, f-tests, coefficient tests) The results of thestudy indicate that the influence of the Effectiveness of Utilizing Social Media (Facebook), asa Promotional Media on Increasing Sales Volume at Surya Foto in Gunungsitoli City, has avalue of 72.6% and 27.4% is influenced by other factors not examined in this study. Based onthe results of the t-test related to the influence of social media (X1) on sales volume (Y), it isknown that social media has a significant effect on sales volume. These results can be seen bylooking at the results of the t-test, where the sig value is 0.000. The sig value is smaller than0.05 (0.000 <0.05) with a calculated t value of 4.072 greater than 0.320 (4.072> 0.320). So itcan be concluded that H0 is rejected and H1 is accepted, meaning that social media has asignificant effect on sales volume.